Increasing the Competency of Water Farmer Farmers Regarding Sales Recording and Marketing Strategies in The Medium Village of Abiansemal Badung - PRILIANDANI, Ni Made Intan; KRISTIANTARI, I Dewa Ayu; SARI, Ni Made Taman (Indonesia Strategic Sustainability, 2024)
Most of the livelihoods of the residents of Medium Village are as water farmers. The obstacle faced by water henna farmers in Sedang Village is the lack of knowledge of farmers in marketing strategies for their water henna flower harvest, apart from that, water henna farmers in Medium Village still have minimal knowledge about the importance of making a daily sales record book. The solution that can be given to overcome this problem is by providing knowledge to water henna farmers in the Medium Village to prepare a sales record book. This is done to help water henna farmers in the Medium Village to be able to know the profits they can make and be able to predict their financial performance. The next solution is to provide knowledge about online marketing media by utilizing social media, this is provided to help water henna farmers in Medium Village to be able to market their crops more widely.